Optimizing the Transfer Process of Air-Rail Integration Services: A Simulation Approach - Fan Jiang; Min Yang; Shiyu Huang (Journal of Advanced Transportation)
With the progress of regional integration in China and the growth of passenger travel demand, a single travel mode has been unable to meet passengers’ cross-regional, multimodal, and personalized travel needs. Air-rail integration service (ARIS) is gradually catching on with travellers. Compared with developed countries, ARIS remains in its infancy in China, with a low penetration rate. Against this backdrop, this study presents an SP survey of ARIS passengers at Shijiazhuang Zhengding International Airport as an example and analyses the factors affecting their transfer process using multiple ordinal logistic regression. The satisfaction analysis results help to construct a simulation model of ARIS of Shijiazhuang Zhengding International Airport by using AnyLogic to verify the optimization effect. The research results show a significant impact on the ARIS transfer process by gender, education, occupation, travel mode, travel cost, location of the shuttle bus, arrival frequency of shuttle bus, manual baggage check-in service, self-service check-in, and the performance of security check equipment. The adoption of optimization measures will reduce ARIS shuttle bus, baggage check-in, and security check-in times by 68%, 50%, and 45%, respectively.